Analisis Sistem Keuntungan Pola Bagi Hasil Nelayan Kelong Apung Pulau Pucung Desa Malang Rapat Kabupaten Bintan - Myrna Sofia; Inge Lengga Sari Munthe (Bahtera Inovasi, 2018)
The local government of Bintan Regency in this case the Department of Marine and Fisheries has allocated funds in the form of fishing gear facilities and infrastructure including kelong. The efforts of the Bintan district government through the Ministry of Marine Affairs and Fisheries have made efforts to improve the welfare of fishermen in Bintan Regency, but whether these efforts have been directly felt by fishermen on the island of Pucung, Malang Village, Bintan District Meeting. Where the majority of fishermen on the coast of Bintan Regency use the Floating Kelong Fishing Equipment. This study aims to determine the profit sharing pattern between kelong owners "Toke" with floating kelong fishermen on Pucung Island Malang Village Bintan District Meeting.. The research was conducted using primary data obtained directly from fishermen in the form of daily reports. The study was conducted for 4 (four) months from April to July 2018. The number of respondents in the study were 78 people. Pucung Island fishermen apply 3 profit sharing patterns for fishing activities using floating kelong, namely: Salary System, 1: 1 and 2: 1.